Adolescents' and young adults' experiences of a prototype cancer smartphone app. (February 2021) - Hanghøj, Signe; Boisen, Kirsten A; Hjerming, Maiken; Pappot, Helle
Objective: Smartphone cancer-related apps have been shown to meet some of the needs of adolescents and young adults (AYAs) during their cancer trajectory. However, there is a lack of apps evaluated by AYAs; thus, the quality of many of these apps has been contested. The aim of this study was to investigate the usefulness of a cancer smartphone app called Kræftværket. The AYA participants reflected on their first experiences of the app and whether it was a relevant and useful tool during and after their cancer trajectory. Methods: A total of 20 AYA cancer patients aged 16-29 years (n = 10 on treatment, n = 10 in follow up) were provided with a prototype of the Kræftværket app during a 6-week test period (April-May 2018). After the test period, n = 17 participated in focus group interviews, which were analyzed thematically. Results: The following themes were found: Sharing personal information (anonymity, safe communication, tough topics, videos and YouTube clips, tracking statistics); Normalcy (Seeing oneself reflected in in others, not alone, general and specific communities); Need for interaction (response from the app, information provided by the app, the app should give more back); and An everyday tool (integrating the app into daily routines, competition between app and Facebook group, temporary needs). Conclusions: The app was perceived to be most relevant at disease onset. During the treatment period, both diagnosis-specific information and communities were requested. There was a call for a clearer distinction between the purpose of the app and other Facebook communities and for a notification function.